Intertextuality and game-based technologies in contemporary film adaptations - Ситникова, Вера (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2016)
The article is devoted to an important aspect of modern aesthetics – intertextuality, which is discussed on the example of film adaptations of Russian classics. Adaptation is considered in the framework of literary-scientific reflection on “translating” verbal text for the audiovisual channel. Procedures connected with intertextuality and game-based technologies are subjected to interpretation in the context of contemporary cinema’s avant-garde artistic searches.